The Effectiveness of Moringa oleifera Burn Healing: In Vivo Study - Duta Indriawan; Najatullah; Trilaksana Nugroho; Neni Susilaningsih (HM Publisher, 2022)
Background: Burns is a type of wound that requires more intensive treatment considering the damage from these wounds is quite massive and very often causes infection. Topical antimicrobials used today have few side effects and are only partially effective in wound healing. The aim of the study was to explore the potential of Moringa oleifera on burn wound healing in vivo. Methods: This study is an experimental study using 24 rats. Rats were grouped into 3 treatment groups and 1 control group. Furthermore, the number of fibroblasts and PMN cells was assessed in the wound tissue. Data analysis was done by univariate and bivariate. Results: The combination of sulfur sulfadiazine and Moringa oleifera was able to significantly increase the number of fibroblasts and reduce PMN cells in burn tissue. Conclusion: Moringa oleifera extract has the potential to accelerate burn healing by inhibiting inflammation and fibroblast activation.